Network-Centric Service Oriented Enterprise - Chang, William Y. (Springer Netherlands : Imprint: Springer, 2007)
There is a major effort underway in the area of network-centric operations that promises to redefine networking applications. These applications have the potential to raise Enterprise operational efficiency to a whole new level. Following the successful invention of TCP/IP and the Internet, which have tremendous economic impacts on our society, the Department of Defense (DoD) is initiating a new IT revolution, based on Global Information Grid (GIG) model, with a focus on performance outcomes of organizational adaptation, survival, and competence. To ignore this technological trend of converging business and process management would be to jeopardize our competitive edge. The emergence of Enterprise services has triggered a major paradigm shift in distributed computing: from Object-Oriented Architecture (OOA) to Service-Oriented Architecture (SOA). As the need grows to incorporate and exchange information across wire-line and wireless networks, so grows the necessity to establish an infrastructure for high-distribution communities in a timely and safe manner. Network-Centric Service-Oriented Enterprise (NSCOE) is seen as heralding the next generation of mainstream Enterprise-business information collaboration solution that can enforce information and decision superiority in the decentralized, loosely-coupled, and highly interoperable service environments. Network-Centric Service Oriented Enterprise establishes a system-of-systems (SoS) view of information technologies, offering a synergistic combination of data and information-processing capacity upon an innovative networked-management framework.